Quality of Health Service: Issues and Measures to Improve - Nepal, Dhruba; Nepal, Yugal Jyoty (Prashasan: The Nepalese Journal of Public Administration, 2021)
Health service is considered fundamental right of every citizen in the Constitution of Nepal, so it obviously becomes obligation of the State. Service quality has many dimensions, among them responsiveness towards patients is an indispensable one. Service quality and health service quality are defined differently by different writers. To improve health service quality, some measures are deemed necessary to be taken immediately. Among them, ingraining a culture of quality and use of technology are primary ones. This article focuses on the problems in health quality and some measures to be adopted in order to improve the service quality.